Massive Multiplayer Online Role-Playing Games to Enrich Vocabulary to Foreign Language Learners: The Implementation - Miftahuddin, Damar; Malihah, Noor (Institut Agama Islam Negeri Kudus, 2022)
Massive Multiplayer Online Role-Playing Games (MMORPGs) are increasingly used to improve language learning. Many games have been created as products to help players improve their learning abilities. This research explores the execution of the MMORPGs to improve their vocabulary. The information was gathered through observation, documentation, and interview. There are seven chosen experienced players of MMORPG in worldwide servers who meet the requirements. Results demonstrated that implementing MMORPG can assist the EFL learners with acquiring new vocabulary from the aspect of the game like socializing, guild, mission, storyline, trading market, and things depiction assist the EFL learners with learning new vocabulary. The results of the study were expected to help the EFL learner gamer learn English, especially vocabulary, since the game has many aspects that help the EFL learners who play this game to enrich their vocabulary.